The submerged footprint of Perito Moreno glacier - Lodolo, Emanuele (2020)
Perito Moreno is the most famous calving glacier of the South Patagonia Icefield, the largest temperate glacier system of the Southern Hemisphere. Unlike most of the glaciers in the region that have strongly retreated in recent decades, the position of Perito Moreno glacier front remained relatively unchanged in the last century. However, earliest photographic documents show that, at the end of the nineteenth century, the front was ca. 800 m behind the current position. There is no reliable information about the positions of the Perito Moreno front in earlier times. Here we show evidence of two subaqueous moraine systems both in the Canal de Los Témpanos and in the Brazo Rico, the two arms of Lago Argentino along which Perito Moreno glacier has flowed over time. These moraines, identified for the first time in the Canal de Los Témpanos from bathymetric and high-resolution seismic profiles, mark the position of the largest glacier advance, tentatively correlated with the moraines of the “Herminita advance” identified and dated onland. We interpret these bedforms as the evidence of the most pronounced advance of Perito Moreno glacier during the mid-Holocene cooling event that characterized this sector of the Southern Hemisphere. This study highlights the importance of subaqueous glacial bedforms, representing decisive records of the glacial history and palaeoclimate, which could help unveiling the origin of the different behavior of glaciers like Perito Moreno that in a warming climate are relatively stable.